Synthetic peptides that inhibit binding of the collagen type II 261-273 epitope to rheumatoid arthritis-associated HLA-DR1 and -DR4 molecules and collagen-specific T-cell responses. - Fridkis-Hareli, M; Rosloniec, E; Fugger, L; Strominger, J (2000)
Copolymer 1 [Cop 1, poly (Y, E, A, K)] is a random synthetic amino acid copolymer effective in the treatment of relapsing forms of multiple sclerosis (MS), a disease that is linked to HLA-DR2 (DRB1*1501). Another copolymer [poly (Y, A, K)] was also identified that binds to rheumatoid arthritis (RA)-associated HLA-DR1 (DRB1*0101) or HLA-DR4 (DRB1*0401) molecules and inhibits the response of HLA-DR1- and -DR4-restricted T cell clones to an immunodominant epitope of collagen type II (CII) 261-273 (a candidate autoantigen in RA). In the present study various peptides have been synthesized based on binding "motifs" of Cop 1 for HLA-DR1 and -DR4 molecules. Those peptides with K at P-1 or K at P8 were particularly effective as inhibitors of binding of CII 261-273, of Cop 1 and of the influenza virus hemagglutinin peptide 306-318 to these class II proteins. Moreover, several of them were also potent inhibitors of the CII 261-273-reactive T cell clones. These findings suggest that small peptides or their more stable derivatives may be able to substitute for copolymers in the treatment of RA, and by implication of MS.